Demethoxycurcumin induces autophagic and apoptotic responses on breast cancer cells in photodynamic therapy. (January 2015) - Lin, Hui-Yi; Lin, Jia-Ni; Ma, Jui-Wen; Yang, Ning-Sun; Ho, Chi-Tang; Kuo, Sheng-Chu; Way, Tzong-Der
Highlights: Curcuminoids may act as photosensitizers which are activated with blue light. The cytotoxic effect of curcuminoids with blue light is more than curcuminoids only. Demethoxycurcumin, the most active compound against different types of breast cancer cell lines, induces autophagy and apoptosis. Abstract: Curcuminoids, including curcumin (CUR), demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC), show the maximum absorption wavelength near blue light. Photodynamic therapy (PDT) has been developed as a therapeutic modality, which could induce cell death via the formation of ROS under illumination. Recently, it has been suggested that curcuminoids may be developed as potential photosensitizers. Here we found that curcuminoids-PDT significantly inhibited cell viability in breast cancer cell lines; in particular DMC-PDT has the highest anti-proliferative effect. A comprehensive analysis of cell response to DMC-PDT showed that autophagy was an early event and apoptosis was a late event. The generation of ROS by exciting the photosensitizer in PDT can activate MAPK pathway. Pre-treatment with a singlet oxygen scavenger or JNK inhibitor in DMC-PDT resulted in the reversion of cell viability, a reduced LC3 conversion and PARP cleavage. These results indicate that DMC may be considered as a new photosensitizer in PDT for cancer treatment.